Analysis of Factors that Influence Taxpayers Compliance of Micro, Small, and Medium Enterprises Restaurant Owner That Uses E-Commerce - Purnama, Handy; Mimba, Ni Putu Sri Harta (E-Jurnal Akuntansi; Vol 34 No 7 (2024)DO - 10.24843/EJA.2024.v34.i07.p20, 2024)
The purpose of this research is to ascertain how tax incentives, tax socialization, and taxpayer knowledge influence taxpayer compliance. The research was conducted through the distribution of questionnaires. The research subjects were 50 samples of  SMEs restaurant owner taxpayers who use e-commerce. The data analysis technique used was multiple regression analysis. This study found that taxpayer compliance was influenced positively by tax incentives and tax knowledge but was unaffected by tax socialization. It can be concluded that MSME taxpayer compliance will increase with tax incentives and tax knowledge. Keywords: Tax incentives; Tax Socialization; Tax Knowledge; Taxpayer Compliance